Mateera – An underutilized cucurbit vegetable of Indian desert - Samadia, D K; Verma, A K (Indian Horticulture, 2022)
Mateera is an under-utilized, drought tolerant and native form of watermelon. It is grown in rainfed areas and its fruits are liked by desert dwellers. Nutritionally rich tender fruits are used for vegetable and ripened for dessert. Fruits and seedkernel are sold at premium price. From 1994, ICAR-CIAH has undertaken intensive research for germplasm conservation and utilization in varietal development. On evaluation of wide range of Citrullus germplasm, watermelon genotypes failed to express their potential under the high temperature conditions. Therefore, promotion of varieties from native germplasm is beneficial and recommended for commercial cultivation under resource constrainted arid region. The developed varieties such as AHW-19 and Thar Manak are early to harvest, producing better quality fruits suitable for multiple-use.